"Estaba bien chiquito" (I Was Very Young): The Transition to Adulthood and "Illegality" of the Mexican and Central American 1.25 Generation. Issue 3 (May 2022) - Diaz-Strong, Daysi Ximena
Knowledge on the transition to adulthood of undocumented immigrants arriving in childhood primarily derives from the experiences of minors arriving below the age of 13 years—or the 1.5 generation. The transition to adulthood of the 1.25 generation—those who immigrate between the ages of 13 and 17 years—has been largely missed. This article examines the salient challenges legal exclusion, or "illegality, " created as the Mexican and Central American 1.25 generation launches into adulthood and the extent that "illegality" disrupts their envisioned futures. Drawing on interviews with 40 undocumented 1.25 generation young adults in Illinois, three distinct patterns were identified: (a) 1.25 generation participants who enrolled in U.S. K–12 schooling, (b) 1.25 generation men who never-enrolled in U.S. K–12 schooling, and (c) 1.25 generation women who never-enrolled. These patterns were shaped by the reasons for their migration, whether the migration process was gendered, and their expectations for adulthood. This article contributes to a more complete picture of the challenges childhood arrivals experience at a critical point of transition in the life course and the sources of variation. Moreover, attention is brought to the timing of immigration—the life-stage when a minor immigrates—as a source of differentiation warranting further consideration.